Molecular characterization and evaluation of Paenibacillus Pabuli strain D12 and D14 isolated from gut microflora of red tilapia as potential probiotics for aquacultural use - Hamdan, Hishammuddin (2014)
Presently, the aquaculture production is facing a greater constraint due to disease outbreaks particularly in the culture of marine and freshwater fish. The application of antibiotics or chemotherapeutics agents continues to be the current method of choice for disease control. However, the evolution of antimicrobial resistance gene among pathogenic bacteria, potential health risk of antibiotic accumulation in humans and growing awareness among public and authorities concern regarding food safety issues has led to the application of probiotics, an environment-friendly and non-pathogenic beneficial bacteria in aquaculture. Therefore, the present investigation has been made to evaluate three bacterial isolates from the gastrointestinal tracts of cultured red tilapia fish as a biocontrol agent against fish pathogenic bacteria. Probionts identification procedures through phylogenetic analysis based on 16S rRNA and Internal Transcribed Spacer (ITS) gene sequencing were constructed as part of precise molecular identification. Their antagonistic ability towards common fish pathogenic bacteria was evaluated using a series of in vitro assessment. Successful candidates were verified in vivo with a bioassay using Artemia to confirm their safety towards these common live-feed organisms. Results derived from ITS profiles identified our probionts as Paenibacillus pabuli strain D12, Paenibacillus pabuli strain D14 and Bacillus megaterium strain E28. As for detection of antagonistic effect, P. pabuli strain D12 and P. pabuli strain D14 were further chosen from cross-streaking method as they exhibited antagonism ability against common fish pathogenic bacteria. Our finding from Bacteriocin Like Inhibition Substance (BLIS) assay suggests P. pabuli strain D12 as the most prominent probiotic since it produced maximum inhibitory capacities against target strains at 109 cfu/mL with 72 hours pre-incubation period of probionts. In broth co-culture assay, complete elimination of V. alginolyticus by P. pabuli strain D12 successfully occurred at 48 hours of incubation period as compared to P. pabuli strain D14 (72 hours). Final in vivo studies validate the outcomes from our in vitro screening test. Artemia survival rate is the highest when treated with P. pabuli strain D12 (72%) followed by P. pabuli strain D14 (68%) after being challenged with V. alginolyticus. Vibrios count in Artemia and in the culture water proved that our probionts suppressed the proliferation of the pathogenic strain, thus could be used as biocontrol agent in fish aquaculture industry via live-feed carrier. The present study proved the ability of P. pabuli strain D12 and D14 as potential probiotics in controlling pathogenic V. alginolyticus in Artemia culture system.